The growth paradox, sustainable development, and business strategy. (4th May 2021) - Edwards, Mark G.
Abstract: Economic growth is a two‐edged sword. Expanding economies and industries create wealth and employment, but global economic expansion is having unprecedented deleterious impacts on vital planetary systems. Despite this, the core strategic goal of all economies and many businesses continues to be the pursuit of ongoing economic growth. To resolve this paradox, a reconceptualization of firm‐level growth is presented. I describe and discuss the organizational characteristics of the growth paradox and follow this with a metatheoretical review of economic, organizational, and ecological perspectives on growth. From this review, a typology of firm‐level strategy is developed that radically reconceptualizes business growth as developmental activity primarily concerned with social–ecological flourishing. The features of this typology and its implications for business strategy are discussed according to three principles that emerged from the analysis: multidexterity, resilience thinking for design, and inclusive balance (embeddedness). Together, these strategy principles form the prerequisite management competencies needed for the development, implementation, and evaluation of sustainable business strategies. Transformative firm‐level responses to the growth paradox are needed if sustaining forms of organizational growth are to be achieved and this paper presents a novel integrative framework for informing those strategies.